A Comparitive Study Between Magnesium Sulphate Versus Dexamethasone as an Adjuvant to Bupivacaine in Supraclavicular Brachial Plexus Block (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Magnesium Sulphate and Dexamethasone are used as adjuvants to local anaesthetics inregional anaesthesia to improve the quality of blockObjective: To compare the efficacy of magnesium sulphate and dexamethasone on the characteristics of theblock and its effect on postoperative analgesia when added as an additive to bupivacaine in supraclavicularbrachial plexus block.Materials and Methods: Fifty patients belonging to American Society of Anaesthesiologists (ASA) GradeI and II, aged between 18 to 55 years, scheduled for elective upper limb surgeries under supraclavicularbrachial plexus block were enrolled in this study. Patients were equally divided into two groups : group Mreceived 0.5% Bupivacaine 30ml with 10% Magnesium sulphate 5 ml (500mg) and group D received 0.5%Bupivacaine 30ml with Dexamethasone 2ml (8mg) + Normal saline 3ml. Onset and duration of sensory andmotor block , duration of postoperative analgesia and any complications were observed.Results: In our study the demographic profile of patients, duration of surgery and ASA status between thetwo groups were comparable. Onset of sensory block was earlier in group D than group M (17.12±0.93minutes and 19.40 ±1.08 minutes respectively, p=0.001). Duration of motor block and analgesia were longerin group D as compared to group M (479.00 ±50.83 minutes vs 346.40 ±32.77 minutes respectively, p=0.001 for motor block and 533.80 ±59.80 minutes vs 415.00 ±57.23 minutes respectively, p=0.001 foranalgesia). No significant side effects were noted.Conclusion: Dexamethasone is a better adjuvant than Magnesium Sulphate when added to bupivacaine insupraclavicular brachial plexus block as it prolongs duration of motor block and analgesia significantly withminimal side effects.
Keywords: Magnesium Sulphate, Dexamethasone, Supraclavicular Brachial plexus block